Language Socialization, Ideological Stance-Taking, and Aspirational Narratives Among Multilingual Filipino Children - Leonardo Tejano (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2026)
This study investigates the language socialization processes, ideological stance-taking, and agentive self-positioning of multilingual Filipino children through an analysis of 100 aspirational narratives. Grounded in language socialization theory, positioning theory, and the framework of language ideologies, the research employs a mixed methods design to examine how children aged eight to nine discursively construct their future social roles. Quantitative frequency analysis of thematic categories is integrated with qualitative discourse analysis of verbatim excerpts. Findings reveal that children encode collectivist ideologies using specific linguistic features, including Ilokano discourse markers, inclusive pronouns, deontic modality, and benefactive constructions. The narratives demonstrate that socialization is a bidirectional process influenced by diverse agents, primarily parents, extended family, peers, teachers, and mass media, who mediate the children's understanding of socioeconomic and environmental vulnerabilities. Furthermore, the children position themselves not merely as future professionals, but as active social agents dedicated to agrarian solidarity, digital equity, disaster preparedness, and nationalist-patriotic advocacy. The study highlights the capacity of young multilingual learners to navigate the inequalities of multilingualism and articulate transformative civic aspirations, offering significant implications for mother tongue-based multilingual education and curriculum development in postcolonial contexts worldwide.